PEWANI cherished tahfiz students with iftar / Suryani Abdul Rahman - Abdul Rahman, Suryani (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
In the spirit of the holy month of Ramadan, the Women’s Association of UiTM Cawangan Perak (PEWANI) was honored to host an iftar or breaking of fast ceremony for the students of Madrasah Tahfiz Firdaus al Warisi, Tapah. The iftar was organised by PEWANI’s welfare bureau and was held at the Islamic Center of UiTM Seri Iskandar Campus on May 23, 2019.